Analisis Implementasi Si Black Berbasis Android Sebagai Upaya Peningkatan Prestasi Belajar Fisika - Ismatulloh, Kholida; Kholiso, Yosi Nur; Arianti, Baiq Desi Dwi; Ropikoh, Ropikoh (Universitas Hamzanwadi, 2023)
This research aims to (1) produce Si Black-based learning media android (2) determines the level of appropriateness of learning media according to material experts, media experts, and users, (3) Efforts to improve the learning achievement of class VIII students on Asas Black. Implementation analysis research is collaborative research between quantitative research and product development. The initial product was validated by media experts and material experts and then revised. The next stage is user testing, and tested on 30 users from NWDI Middle School. Next, there was a summative test on 40 students at SMPN 3 Selong. Results research shows that (1) the Black product is very suitable for use in the physics learning process as proven by the average score by media experts of 93.5 and material experts of 91.25 in the